APPROACHING THE MARITIME SOUTHEAST ASIA FROM THE MARGINS. A TALE OF MUHAMMAD SALEH, A MINANGKABAU WEST COAST MERCHANT OF THE NINETEENTH CENTURY SUMATRA - Mestika Zed (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2017)
West coast of Sumatra, which was relatively remote from major centers laying on the Malacca Straits, had a lengthy history of trading contacts with the maritime Southeast Asia, especially with the Indian Ocean basins. The paper asks whether the trajectories of broader historical development of maritime Southeast Asia can be informed by way of tracing developments among the small localcontexts as evidenced in the case of the fate of Muhammad Saleh, a Minangkabau west coastal merchant of the 19 th century Sumatra. In other words, it asks if the sea trading routes underpinning integration of the archipelagic countries are also partly valid for the world west coast of Sumatra in the early-modern era. This paper will help us to appreciate our maritime world, how we got to where we are now, and identify constants and trends that will assist in our understanding of maritime Southeast Asia today and in the future.